Cytoprotective Properties of a New Nanocomplex of Selenium with Taxifolin in the Cells of the Cerebral Cortex Exposed to Ischemia/Reoxygenation - Elena G. Varlamova; Venera V. Khabatova; Sergey V. Gudkov; Egor Y. Plotnikov; Egor A. Turovsky (MDPI AG, 2022)
The neuroprotective effect of the natural antioxidant taxifolin (TAX) is well known for ischemic pathologies. However, the limitations of taxifolin application are described-poor solubility, low ability to penetrate the blood-brain barrier, and side effects from high doses for stroke therapy. We proposed the problem of targeted delivery of taxifolin and achievement effective concentrations could be solved by developing a nanocomplex of selenium nanoparticles (SeNPs) with taxifolin (Se-TAX). In this study, we developed a selenium-taxifolin nanocomplex based on selenium nanoparticles with a 100 nm size. It was shown that TAX, SeNPs, and Se-TAX were all able to suppress the production of ROS in neurons and astrocytes under exposure to exogenous H2O2 and ischemia-like conditions. However, the Se-TAX nanocomplex appeared to be the most effective, displaying a lower working concentration range and negligible pro-oxidant effect compared with pure SeNPs. The mechanism of Se-TAX beneficial effects involved the activation of some antioxidant enzymes and the suppression of ROS-generating systems during OGD/reoxygenation, while TAX and "naked" SeNPs were less effective in regulating the cellular redox status. Naked SeNPs inhibited a global increase in Ca2+ ions in cytosol, but not OGD-induced hyperexcitation of the neuroglial network, while Se-TAX suppressed both [Ca2+]i rise and hyperexcitation. The effect of TAX at similar doses appeared exclusively in inhibiting OGD-induced hyperexcitation. Analysis of necrosis and apoptosis after OGD/reoxygenation revealed the highest efficiency of the Se-TAX nanocomplex as well. Se-TAX suppressed the expression of proinflammatory and proapoptotic proteins with simultaneous activation of protective genes. We conclude that the Se-TAX nanocomplex combines the antioxidative features taxifolin and the antiapoptotic effect of nanoselenium, involving the regulation of Ca2+ dynamics.